Preparation method of nano copper powder
By using a modified protective agent containing benzotriazole and fluorine in the preparation of nanocopper powder, the problem of insufficient oxidation resistance and influence of conductivity at high temperatures is solved, and the excellent oxidation resistance and conductivity of nanocopper powder are achieved.
Patent Information
- Application Number
- CN202411916368.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing nano copper powder preparation methods have problems with agglomeration and oxidation, especially at high temperatures, which lack oxidation resistance and electrical conductivity are affected.
Nanocopper powder is prepared by copolymerizing a modified monomer containing benzotriazole and fluorine with pyrrole in liquid phase reduction method, and reacting with a copper salt and a reducing agent. The modifier forms a tight adsorption film layer through complexation and electrostatic adsorption, enhancing oxidation resistance and electrical conductivity.
The excellent oxidation resistance and conductivity of nano copper powder are achieved, and it still has high oxidation resistance, avoiding agglomeration and oxidation, and maintaining conductive properties.
Smart Images

Figure BDA0005206912100000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material preparation, and in particular to a method for preparing nano copper powder. Background Art
[0002] Nano copper powder has attracted attention due to its high electrical and thermal conductivity, low electrochemical migration behavior, strong solderability, low price and readily available raw materials, and has become an important functional material in the fields of modern military industry, shipbuilding, aerospace and cutting-edge technology. Nano copper powder can be prepared by reacting an ionic copper precursor with a reducing agent in a solvent, or by direct thermal decomposition of the precursor, mainly including electrolysis, microemulsion, sol-gel, hydrothermal and liquid phase reduction. Among them, the liquid phase reduction method is the most commonly used and most industrially promising preparation method. The liquid phase reduction method uses the mechanism of redox reaction. In the liquid phase or near the liquid phase, the reactants react chemically under the action of the reducing agent to prepare nanoparticles.
[0003] The liquid phase reduction method can generate a large number of nano copper particles in a short period of time, but it has the disadvantage that the generation speed of nano copper particles is too fast to be controlled, and the newly generated nano copper particles have a high surface energy and are very easy to agglomerate. In addition, the high activity of copper causes it to oxidize rapidly when exposed to air. Therefore, how to reduce agglomeration and increase antioxidant capacity during the preparation and post-treatment of nano copper is a research focus. It is often necessary to add a certain amount of protective agent or dispersant to reduce the surface activity of nano copper particles and prevent agglomeration and oxidation.
[0004] Benzotriazole is the most widely used corrosion inhibitor in the anti-oxidation treatment of copper powder. It can form an adsorption film on the surface of nano copper powder by complexation. It has a certain chemical inertness to highly corrosive sulfur dioxide and hydrogen sulfide, and can effectively prevent the oxidation of copper powder. However, benzotriazole has a good effect on the antioxidant performance of copper powder at room temperature, but is not suitable for antioxidant at high temperature. Polyvinyl pyrrolidone, polyethylene glycol and other polymers are often used as protective agents that can expand the thickness of the polymer adsorption layer to increase steric hindrance, so that the nano copper particles are dispersed, thereby effectively preventing agglomeration and increasing the stability of nano copper particles. However, the adsorption layer formed by polymers with poor conductivity such as polyethylene glycol may have an adverse effect on the conductivity of nano copper powder, which is not conducive to the use of nano copper powder in conductive materials. Polypyrrole is a polymer with good conductivity and heat resistance, but polypyrrole has good hydrophilicity, and water accumulation will lead to aggravated oxidation of nano copper powder, resulting in the use of polypyrrole as a protective agent in the liquid phase reduction method to prepare nano copper powder.
[0005] Therefore, a suitable modification method is needed to improve the hydrophilicity of polypyrrole and use it as a protective agent to prepare copper nanopowder, improve the defect of benzotriazole on the insufficient oxidation resistance of nano-copper powder at high temperature, and thus obtain a method for preparing nano-copper powder with excellent properties such as oxidation resistance and conductivity. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing nano copper powder.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A nano copper powder, the preparation of which comprises the following steps:
[0009] Step S1, adding perfluorobutylethylene to dichloromethane, stirring for 30-40 minutes, then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 5-6 hours to obtain an epoxy product; in a protective gas atmosphere, adding a carboxylic acid containing benzotriazole to toluene, heating to 45-50° C., adding pyridine, stirring, then adding the epoxy product, stirring and reacting for 9-10 hours, then heating to 100-110° C., stirring for 1-1.5 hours, and obtaining a fluorinated benzotriazole;
[0010] Further, the amount ratio of perfluorobutylethylene, dichloromethane, and 3-chloroperoxybenzoic acid is 13-15 g: 50-60 mL: 9-10 g; the amount ratio of the carboxylic acid containing benzotriazole, toluene, pyridine, and epoxy product is 9.5-10.5 g: 60-70 mL: 2-2.5 g: 13.5-14.5 g, and the carboxylic acid containing benzotriazole is selected from one of 1-methyl-1,2,3-benzotriazole-5-carboxylic acid and 1-ethyl-1H-benzo[D][1,2,3]triazole-5-carboxylic acid;
[0011] During the reaction of step S1, the carbon-carbon double bond of perfluorobutylethylene is oxidized to an epoxy group to obtain an epoxy product; the carboxyl group of the carboxylic acid containing benzotriazole reacts with the epoxy group of the epoxy product to form a hydroxyl-containing fluorinated benzotriazole;
[0012] Step S2, adding an unsaturated carboxylic acid to DMF, adding thionyl chloride under stirring, and reacting under reflux and stirring at 45-55° C. for 20-22 hours to obtain an acyl chloride product; stirring and mixing fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution a; adding the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution b, and dripping the mixed solution b into the mixed solution a in an ice water bath, and after the dripping is completed, heating to 40-45° C., stirring and reacting at a constant temperature for 8-10 hours to obtain a modified monomer;
[0013] Further, the dosage ratio of unsaturated carboxylic acid, DMF and dichlorothionyl is 4.5-7g:30-40mL:6-7g, and the unsaturated carboxylic acid is selected from one of 3-butenoic acid, 5-hexenoic acid and 7-octenoic acid; the dosage ratio of fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide in the mixed solution a is 24-25g:0.04-0.06g:5.5-6.5g:70-80mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in the mixed solution b is 5.5-7.5g:20-30mL; the dosage ratio of the mixed solution a and the mixed solution b is 75-85mL:30-40mL;
[0014] During the reaction of step S2, the unsaturated carboxylic acid reacts with thionyl chloride to generate an acyl chloride product; the hydroxyl group in the fluorinated benzotriazole reacts with the acyl chloride product to obtain a modified monomer containing a terminal carbon-carbon double bond;
[0015] Step S3, adding the modified monomer to dodecylbenzenesulfonic acid, ultrasonically oscillating for 15-25 minutes, then adding pyrrole and stirring for 30-40 minutes, then dropping ferric chloride solution, stirring and reacting in an ice water bath for 7-8 hours, then centrifuging, washing, and vacuum drying to obtain a modified protective agent;
[0016] Further, the usage ratio of the modified monomer, dodecylbenzenesulfonic acid, pyrrole and ferric chloride solution is 1-1.2 g: 55-65 mL: 2.3-2.5 g: 50-55 mL, and the concentration of the ferric chloride solution is 0.29-0.31 mol / L;
[0017] During the reaction of step S3, under the action of ferric chloride, the modified monomer and pyrrole are copolymerized to obtain a modified protective agent containing benzotriazole and fluorine;
[0018] Step S4, mixing copper salt, reducing agent, modifying protective agent and solvent and heating to 130-150° C., continuing to stir and react for 3-3.5 hours, cooling, washing, centrifuging and drying to obtain nano copper powder;
[0019] Furthermore, the copper salt is selected from one of anhydrous copper chloride, copper sulfate pentahydrate and copper nitrate, and the concentration of the copper salt is controlled to be 3-4 mol / L by adding a solvent; the ratio of the reducing agent to the copper salt is 2-4 mol:1 mol, and the reducing agent is L-ascorbic acid; the ratio of the modified protective agent to the copper salt is 120-140 g:1 mol; and the solvent is ethylene glycol;
[0020] During the reaction of step S4, a liquid phase reduction method is adopted to prepare nano copper powder.
[0021] Beneficial effects of the invention: The invention discloses a method for preparing nano copper powder, wherein the nano copper powder is prepared by using a modified protective agent obtained by copolymerizing a modified monomer containing benzotriazole and fluorine with pyrrole in a liquid phase reduction method to react with a copper salt, a reducing agent, and the like. Benzotriazole can be strongly combined with the surface of nano copper powder through complexation, polypyrrole can be adsorbed on the surface of nano copper powder through electrostatic action, metal-organic coordination generated by nitrogen atoms and the surface of nano copper powder particles, and the intramolecular synergistic effect of benzotriazole and polypyrrole in the modified protective agent enables the surface of the nano copper powder to form a tight adsorption film layer with a certain thickness, generating a steric hindrance effect, thereby effectively preventing the agglomeration and oxidation between the nano copper powder particles; the introduction of fluorine enhances the hydrophobicity of the modified protective agent, making up for the fact that the strong hydrophilicity of polypyrrole may cause the nano copper powder to be corroded by water and cause the oxidation to intensify; the polypyrrole in the modified protective agent has a strong conductivity, which is conducive to maintaining the conductivity of the nano copper powder, and avoids the adverse effect of the adsorption layer formed by using a high molecular polymer with poor conductivity as a protective agent on the conductivity of the nano copper powder; in addition, the modified protective agent has a high heat resistance of polypyrrole, so that the nano copper powder still has a high oxidation resistance at high temperature, making up for the deficiency that corrosion inhibitors such as benzotriazole are not suitable for making the nano copper powder have good oxidation resistance at high temperature.
[0022] Therefore, the nano copper powder of the present invention has excellent oxidation resistance and electrical conductivity, and is worthy of popularization and use. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A nano copper powder, the preparation of which comprises the following steps:
[0026] Step S1, adding perfluorobutylethylene to dichloromethane, stirring for 30 minutes, then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding 1-methyl-1,2,3-benzotriazole-5-carboxylic acid to toluene, heating to 45°C, adding pyridine, stirring, then adding the epoxy product, stirring and reacting for 9 hours, then heating to 100°C, stirring for 1 hour, and obtaining fluorinated benzotriazole; the dosage ratio of perfluorobutylethylene, dichloromethane, and 3-chloroperoxybenzoic acid is 13g:50mL:9g; the dosage ratio of 1-methyl-1,2,3-benzotriazole-5-carboxylic acid, toluene, pyridine and epoxy product is 9.5g:60mL:2g:13.5g;
[0027] Step S2, adding 3-butenoic acid to DMF, adding dichlorothionyl under stirring, and reacting under reflux and stirring at 45° C. for 20 hours to obtain an acyl chloride product; stirring and mixing fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution a; adding the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution b, and dripping the mixed solution b into the mixed solution a in an ice water bath. After the dripping is completed, the temperature is raised to 40° C., and the mixture is stirred at a constant temperature for 8 hours. , that is, the modified monomer is obtained; the dosage ratio of 3-butenoic acid, DMF, and dichlorothionyl is 4.5g:30mL:6g; the dosage ratio of fluorinated benzotriazole, pyridine, triethylamine, and dimethyl sulfoxide in the mixed solution a is 24g:0.04g:5.5g:70mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution b is 5.5g:20mL; the dosage ratio of the mixed solution a and the mixed solution b is 75mL:30mL;
[0028] Step S3, adding the modified monomer to dodecylbenzenesulfonic acid, ultrasonically oscillating for 15 minutes, then adding pyrrole and stirring for 30 minutes, then dropping ferric chloride solution, stirring and reacting in an ice-water bath for 7 hours, then centrifuging, washing, and vacuum drying to obtain a modified protective agent; the amount ratio of the modified monomer, dodecylbenzenesulfonic acid, pyrrole and ferric chloride solution is 1g:55mL:2.3g:50mL, and the concentration of the ferric chloride solution is 0.29mol / L;
[0029] Step S4, mixing and stirring the copper salt, the reducing agent, the modified protective agent, and the solvent and heating to 130° C., continuing the stirring reaction for 3 hours, cooling, washing, centrifuging, and drying to obtain nano copper powder; the copper salt is anhydrous copper chloride, and the solvent is added to control the copper salt concentration to 3 mol / L; the reducing agent and the copper salt are used in a ratio of 2 mol:1 mol, and the reducing agent is L-ascorbic acid; the modified protective agent and the copper salt are used in a ratio of 120 g:1 mol; and the solvent is ethylene glycol.
[0030] Example 2
[0031] A nano copper powder, the preparation of which comprises the following steps:
[0032] Step S1, adding perfluorobutylethylene to dichloromethane, stirring for 35 minutes, then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 5.5 hours to obtain an epoxy product; in a nitrogen atmosphere, adding 1-methyl-1,2,3-benzotriazole-5-carboxylic acid to toluene, heating to 47°C, adding pyridine, stirring, then adding the epoxy product, stirring and reacting for 9.5 hours, then heating to 105°C, stirring for 1.2 hours, and obtaining fluorinated benzotriazole; the dosage ratio of perfluorobutylethylene, dichloromethane, and 3-chloroperoxybenzoic acid is 14g:55mL:9.5g; the dosage ratio of 1-methyl-1,2,3-benzotriazole-5-carboxylic acid, toluene, pyridine, and epoxy product is 10g:65mL:2.3g:14g;
[0033] Step S2, adding 5-hexenoic acid to DMF, adding thionyl chloride under stirring, and reacting under reflux and stirring at 50° C. for 21 hours to obtain an acyl chloride product; stirring and mixing fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution a; adding the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution b, and dripping the mixed solution b into the mixed solution a in an ice water bath. After the dripping is completed, the temperature is raised to 42° C., and the mixture is stirred at a constant temperature for 9 hours. , that is, the modified monomer is obtained; the dosage ratio of 5-hexenoic acid, DMF, and dichlorothionyl is 6g:35mL:6.5g; the dosage ratio of fluorinated benzotriazole, pyridine, triethylamine, and dimethyl sulfoxide in the mixed solution a is 24.5g:0.05g:6g:75mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution b is 6.5g:25mL; the dosage ratio of the mixed solution a and the mixed solution b is 80mL:35mL;
[0034] Step S3, adding the modified monomer to dodecylbenzenesulfonic acid, ultrasonically oscillating for 20 minutes, then adding pyrrole and stirring for 35 minutes, then dropping ferric chloride solution, stirring and reacting in an ice water bath for 7.5 hours, then centrifuging, washing, and vacuum drying to obtain a modified protective agent; the amount ratio of the modified monomer, dodecylbenzenesulfonic acid, pyrrole and ferric chloride solution is 1.1g:60mL:2.4g:52mL, and the concentration of the ferric chloride solution is 0.30mol / L;
[0035] Step S4, mixing and stirring the copper salt, the reducing agent, the modified protective agent, and the solvent and heating to 140°C, continuing the stirring reaction for 3.3 hours, cooling, washing, centrifuging, and drying to obtain nano copper powder; the copper salt is copper sulfate pentahydrate, and the solvent is added to control the copper salt concentration to 3.5 mol / L; the reducing agent and the copper salt are used in a ratio of 3 mol:1 mol, and the reducing agent is L-ascorbic acid; the modified protective agent and the copper salt are used in a ratio of 130 g:1 mol; and the solvent is ethylene glycol.
[0036] Example 3
[0037] A nano copper powder, the preparation of which comprises the following steps:
[0038] Step S1, adding perfluorobutylethylene to dichloromethane, stirring for 40 minutes, then adding 3-chloroperoxybenzoic acid, stirring and reacting at room temperature for 6 hours to obtain an epoxy product; in a nitrogen atmosphere, adding 1-ethyl-1H-benzo[D][1,2,3]triazole-5-carboxylic acid to toluene, heating to 50°C, adding pyridine, stirring, then adding the epoxy product, stirring and reacting for 10 hours, then heating to 110°C, stirring for 1.5 hours, and obtaining fluorinated benzotriazole; the amount ratio of perfluorobutylethylene, dichloromethane, and 3-chloroperoxybenzoic acid is 15g:60mL:10g; the amount ratio of 1-ethyl-1H-benzo[D][1,2,3]triazole-5-carboxylic acid, toluene, pyridine, and epoxy product is 10.5g:70mL:2.5g:14.5g;
[0039] Step S2, adding 7-octenoic acid to DMF, adding thionyl chloride under stirring, and refluxing and stirring at 55° C. for 22 hours to obtain an acyl chloride product; stirring and mixing fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution a; adding the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution b, and dripping the mixed solution b into the mixed solution a in an ice water bath. After the dripping is completed, the temperature is raised to 45° C. and stirred at a constant temperature for 10 h, that is, the modified monomer is obtained; the dosage ratio of 7-octenic acid, DMF, and dichlorothionyl is 7g:40mL:7g; the dosage ratio of fluorinated benzotriazole, pyridine, triethylamine, and dimethyl sulfoxide in the mixed solution a is 25g:0.06g:6.5g:80mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution b is 7.5g:30mL; the dosage ratio of the mixed solution a and the mixed solution b is 85mL:40mL;
[0040] Step S3, adding the modified monomer to dodecylbenzenesulfonic acid, ultrasonically oscillating for 25 minutes, then adding pyrrole and stirring for 40 minutes, then dropping ferric chloride solution, stirring and reacting in an ice water bath for 8 hours, then centrifuging, washing, and vacuum drying to obtain a modified protective agent; the amount ratio of the modified monomer, dodecylbenzenesulfonic acid, pyrrole and ferric chloride solution is 1.2g:65mL:2.5g:55mL, and the concentration of the ferric chloride solution is 0.31mol / L;
[0041] Step S4, mixing and stirring the copper salt, the reducing agent, the modified protective agent and the solvent and heating to 150° C., continuing the stirring reaction for 3.5 hours, cooling, washing, centrifuging and drying to obtain nano copper powder; the copper salt is selected from one of anhydrous copper chloride, copper sulfate pentahydrate and copper nitrate, and the solvent is added to control the copper salt concentration to be 4 mol / L; the reducing agent and the copper salt are used in a ratio of 4 mol:1 mol, and the reducing agent is L-ascorbic acid; the modified protective agent and the copper salt are used in a ratio of 140 g:1 mol; and the solvent is ethylene glycol.
[0042] Comparative Example 1
[0043] Compared with Example 3, perfluorobutylethylene was replaced with 1-hexene, fluorine was not introduced, and the rest was exactly the same as Example 3 to obtain nano copper powder.
[0044] Comparative Example 2
[0045] Compared with Example 3, the carboxylic acid containing benzotriazole was replaced with benzoic acid, benzotriazole was not introduced, and the rest was exactly the same as Example 3 to obtain nano copper powder.
[0046] Comparative Example 3
[0047] Compared with Example 3, the modified protective agent in step S4 is replaced by the fluorinated benzotriazole in step S1, polypyrrole is not introduced, and the rest is exactly the same as in Example 3 to obtain nano copper powder.
[0048] The nano copper powder prepared by the present invention is further tested for its effect, and the test results are as follows.
[0049] Antioxidation: Place the nano copper powder in a ventilated environment indoors, expose it to air, and then measure the mass growth percentage of the nano copper powder after 30 days;
[0050] Oxidation resistance at 200°C: Place the nano-copper powder in an air oven at 200°C, and then measure the mass growth percentage of the nano-copper powder after 30 days;
[0051] Electrical conductivity: The electrical conductivity is tested by eddy current method, and its value is the ratio of the electrical conductivity of the obtained nano copper powder to the electrical conductivity of the pure nano copper powder;
[0052] The test results are recorded in Table 1;
[0053] Table 1: Test results
[0054]
[0055] According to the data in Table 1, the nano copper powder of the present invention has excellent oxidation resistance and electrical conductivity. It can be seen from Example 3 compared with Comparative Example 1 that fluorine is not introduced into the modified protective agent, the hydrophobicity of the modified protective agent decreases, and the strong hydrophilicity of polypyrrole cannot be compensated for, which may cause the nano copper powder to be eroded by water and aggravate oxidation, thereby causing the oxidation resistance of the nano copper powder to decrease. It can be seen from Example 3 compared with Comparative Example 2 that benzotriazole is not introduced into the modified protective agent, and intramolecular synergy with polypyrrole cannot be produced to form a tight adsorption film layer with a certain thickness on the surface of the nano copper powder, and the oxidation resistance of the nano copper powder decreases. It can be seen from Example 3 compared with Comparative Example 3 that fluorine-containing benzotriazole is used as a protective agent, and polypyrrole is not introduced, and the oxidation resistance, oxidation resistance at high temperature, and electrical conductivity of the nano copper powder all decrease.
[0056] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing nano copper powder, characterized in that: The steps include: Step S1, adding perfluorobutylethylene to dichloromethane, and reacting with 3-chloroperoxybenzoic acid to obtain an epoxy product; in a protective gas atmosphere, adding a carboxylic acid containing benzotriazole to toluene, adding pyridine, and reacting with the epoxy product to obtain a fluorinated benzotriazole; Step S2, adding an unsaturated carboxylic acid into DMF, and reacting with thionyl chloride to obtain an acyl chloride product; The fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution a; the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution b; the mixed solution a and the mixed solution b are mixed, stirred and reacted to obtain a modified monomer; Step S3, adding the modified monomer to dodecylbenzenesulfonic acid, then adding pyrrole, and then dropping ferric chloride solution, stirring and reacting to obtain a modified protective agent; Step S4, mixing and stirring the copper salt, the reducing agent, the modifying protective agent and the solvent to obtain nano copper powder.
2. The method for preparing nano copper powder according to claim 1, wherein: In step S1, the usage ratio of perfluorobutylethylene, dichloromethane and 3-chloroperbenzoic acid is 13-15 g: 50-60 mL: 9-10 g.
3. The method for preparing nano copper powder according to claim 1, wherein: In step S1, the usage ratio of the carboxylic acid containing benzotriazole, toluene, pyridine and epoxy product is 9.5-10.5 g: 60-70 mL: 2-2.5 g: 13.5-14.5 g.
4. The method for preparing nano copper powder according to claim 1, characterized in that: In step S1, the benzotriazole-containing carboxylic acid is selected from one of 1-methyl-1,2,3-benzotriazole-5-carboxylic acid and 1-ethyl-1H-benzo[D][1,2,3]triazole-5-carboxylic acid.
5. The method for preparing nano copper powder according to claim 1, characterized in that: In step S2, the usage ratio of the unsaturated carboxylic acid, DMF and thionyl chloride is 4.5-7 g: 30-40 mL: 6-7 g, and the unsaturated carboxylic acid is selected from one of 3-butenoic acid, 5-hexenoic acid and 7-octenoic acid.
6. The method for preparing nano copper powder according to claim 1, characterized in that: In step S2, the usage ratio of fluorinated benzotriazole, pyridine, triethylamine and dimethyl sulfoxide in the mixed solution a is 24-25 g: 0.04-0.06 g: 5.5-6.5 g: 70-80 mL.
7. The method for preparing nano copper powder according to claim 1, characterized in that: In step S2, the usage ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution b is 5.5-7.5 g: 20-30 mL; the usage ratio of the mixed solution a and the mixed solution b is 75-85 mL: 30-40 mL.
8. The method for preparing nano copper powder according to claim 1, characterized in that: In step S3, the usage ratio of the modified monomer, dodecylbenzenesulfonic acid, pyrrole and ferric chloride solution is 1-1.2 g: 55-65 mL: 2.3-2.5 g: 50-55 mL, and the concentration of the ferric chloride solution is 0.29-0.31 mol / L.
9. The method for preparing nano copper powder according to claim 1, characterized in that: In step S4, the copper salt is selected from one of anhydrous copper chloride, copper sulfate pentahydrate and copper nitrate, and a solvent is added to control the concentration of the copper salt to 3-4 mol / L.
10. The method for preparing nano copper powder according to claim 1, characterized in that: In step S4, the ratio of the reducing agent to the copper salt is 2-4 mol:1 mol, and the reducing agent is L-ascorbic acid; the ratio of the modified protective agent to the copper salt is 1.5-2.5 mol:1 mol, and the solvent is ethylene glycol.